Information security management : concepts and practice - Raggad, Bel G. (CRC Press/Taylor & Francis, 2010)
Information security cannot be effectively managed unless secure methods and standards are integrated into all phases of the information security life cycle. And, although the international community has been aggressively engaged in developing security standards for network and information security worldwide, there are few textbooks available that provide clear guidance on how to properly apply the new standards in conducting security audits and creating risk-driven information security programs.